2011
DOI: 10.1021/ja2045925
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized [1-13C]-Ascorbic and Dehydroascorbic Acid: Vitamin C as a Probe for Imaging Redox Status in Vivo

Abstract: Dynamic nuclear polarization (DNP) of 13C-labeled metabolic substrates in vitro and their subsequent intravenous administration allow both the location of the hyperpolarized substrate and the dynamics of its subsequent conversion into other metabolic products to be detected in vivo. We report here the hyperpolarization of [1-13C]-ascorbic acid (AA) and [1-13C]-dehydroascorbic acid (DHA), the reduced and oxidized forms of vitamin C, respectively, and evaluate their performance as probes of tumor redox state. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
145
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(151 citation statements)
references
References 51 publications
4
145
0
2
Order By: Relevance
“…We have demonstrated that tumour extracellular pH can be imaged from the ratio of the signal intensities of hyperpolarised H 13 CO 3 and 13 CO 2 following intravenous injection of hyperpolarised H 13 CO 3 [59] and, more recently, that the tumour redox state can be determined by monitoring the oxidation and reduction of hyperpolarised [1][2][3][4][5][6][7][8][9][10][11][12][13] C]ascorbate and [1][2][3][4][5][6][7][8][9][10][11][12][13] C]dehydroascorbate, the reduced and oxidised forms of vitamin C, respectively [60] (Figure 6). The polarised bicarbonate experiment showed, as expected, that the tumour extracellular space has a low pH, as has been observed using other MR probes in pre-clinical animal models [61].…”
Section: Monitoring the Tumour Microenvironment: Ph And Redox Statementioning
confidence: 99%
“…We have demonstrated that tumour extracellular pH can be imaged from the ratio of the signal intensities of hyperpolarised H 13 CO 3 and 13 CO 2 following intravenous injection of hyperpolarised H 13 CO 3 [59] and, more recently, that the tumour redox state can be determined by monitoring the oxidation and reduction of hyperpolarised [1][2][3][4][5][6][7][8][9][10][11][12][13] C]ascorbate and [1][2][3][4][5][6][7][8][9][10][11][12][13] C]dehydroascorbate, the reduced and oxidised forms of vitamin C, respectively [60] (Figure 6). The polarised bicarbonate experiment showed, as expected, that the tumour extracellular space has a low pH, as has been observed using other MR probes in pre-clinical animal models [61].…”
Section: Monitoring the Tumour Microenvironment: Ph And Redox Statementioning
confidence: 99%
“…Moreover, according the observation first reported in [10,14], trace amounts (1-2 mM) of gadolinium complexes added to the solutions can further improve the DNP signal enhancement. The addition of gadolinium, now commonly exploited in standard protocols for DNP sample preparation [15][16][17], was shown to affect neither the electron linewidth nor the nuclear spin-lattice relaxation time, while it induces a significant reduction of the electron spin relaxation time T 1e [10,18,19]. In the Borghini's framework, however, such reduction would affect the nuclear polarization by less than 10 % [10], whereas the gadolinium-induced enhancement observed experimentally is up to four-fold.…”
Section: Introductionmentioning
confidence: 99%
“…Further developments are in progress to exploit additional benefits of spatiotemporal encoding, such as a built-in restricted FOV capability [24,26], multi-echo experiments and parallel imaging acquisition [34]. Representative metabolic images from a rat following injection of hyperpolarized [1][2][3][4][5][6][7][8][9][10][11][12][13] …”
Section: Discussionmentioning
confidence: 99%
“…DNP can result in signal enhancements >10,000 for 13 C; an unprecedented increase that is leading to new opportunities for imaging pathology and monitoring treatment [3][4][5][6][7]. Pyruvic acid has emerged as the principal 13 C-labeled agent in d-DNP, but there is significant on-going research to develop other compounds for dynamic imaging of metabolism [8][9][10]. Despite this unique potential, in vivo d-DNP 13 C NMR remains a challenge.…”
Section: Introductionmentioning
confidence: 99%